An epistatic effect of the female specific loci on the development of autoimmune vasculitis and antinuclear autoantibody in murine lupus. Issue 4 (8th September 2005) - Zhang, M-C; Misu, N; Furukawa, H; Watanabe, Y; Terada, M; Komori, H; Miyazaki, T; Nose, M; Ono, M
Abstract : Objective: To identify the genetic loci regulating the incidence and severity of renal autoimmune vasculitis developed in murine lupus. Methods: Vasculitis of renal arteries was histopathologically evaluated in MRL/Mp- Fas lpr (MRL/lpr), C57BL/6- Fas lpr (B6/lpr), (MRL/lpr×B6/lpr) F1, and MRL/lpr×(MRL/lpr×B6/lpr) F1 backcross mice. Using genomic DNA samples of the backcross mice, genome-wide scans, association studies, and linkage analyses were carried out based on genotypes of polymorphic microsatellite markers. Correlations of vasculitis grade and levels of various autoantibodies were also evaluated. Results: Two recessive susceptibility loci of the MRL allele were identified on chromosomes 4 and 1, which had previously been defined as the autoimmune related loci termed Arvm1 and Sle-1/Nba2, respectively. The former was epistatic to the latter in a female specific manner. The titre of antinuclear autoantibody (ANA) in IgG class, but not ANA in IgM class or anti-dsDNA in either IgG or IgM class, correlated significantly with vasculitis grade. Conclusions: The present loci have been reported in previous studies using a different set of murine strains, suggesting that they are of importance in the development of autoimmune vasculitis in murine models. The concomitance of autoimmune vasculitis and IgG ANA suggests a shared genetic factor regulating these traits.